A perspective on oligonucleotide therapy: Approaches to patient customization - Thakur, Shikha; Sinhari, Apurba; Jain, Priti; Jadhav, Hemant R. (Frontiers in Pharmacology, 2022)
It is estimated that the human genome encodes 15% of proteins that are considered to be disease-modifying. Only 2% of these proteins possess a druggable site that the approved clinical candidates target. Due to this disparity, there is an immense need to develop therapeutics that may better mitigate the disease or disorders aroused by non-druggable and druggable proteins or enzymes. The recent surge in approved oligonucleotide therapeutics (OT) indicates the imminent potential of these therapies. Oligonucleotide-based therapeutics are of intermediate size with much-improved selectivity towards the target and fewer off-target effects than small molecules. The OTs include Antisense RNAs, MicroRNA (MIR), small interfering RNA (siRNA), and aptamers, which are currently being explored for their use in neurodegenerative disorders, cancer, and even orphan diseases. The present review is a congregated effort to present the past and present of OTs and the current efforts to make OTs for plausible future therapeutics. The review provides updated literature on the challenges and bottlenecks of OT and recent advancements in OT drug delivery. Further, this review deliberates on a newly emerging approach to personalized treatment for patients with rare and fatal diseases with OT.